An intralinguodidactic reform of STEM English curricular design: a case study of scientific literature reading - Yanfeng Yue (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
To match the teaching demands of STEM talents with global competence, an innovative intralinguodidactic methodological approach has been designed and experimented in curricular constructions of STEM English education. In this research project, the construction of English reading course is focused on achieving the training aim of global competence. The aim of this paper is to develop a practical curricular framework of Scientific Literature Reading on the methodological base of intralinguodidactics. The object of this paper is to evaluate the intralinguodidactic curricular framework of STEM English course. The subject is to examine the effectiveness of employing intralinguodidactics as a methodological basis for curricular design. The relevance of this project has been proven by the teaching practice in three aspects: interconnection, decentration, and compatibility. The teaching practice proves that global competence is a set of knowledge, skills, competencies and personal qualities allowing STEM talents to develop communicative competence of a foreign language. And global competence is shaped by future careers of a graduate. Hence, the educational process of STEM English acquires a new meaning, that is, it becomes a process of the autonomous cognition and digestion of English information literacy materials entertaining professional and sociocultural significance.